miRNA-491-5p and GIT1 Serve as Modulators and Biomarkers for Oral Squamous Cell Carcinoma Invasion and Metastasis - Huang, Wei-Chieh; Chan, Shih-Hsuan; Jang, Te-Hsuan; Chang, Jer-Wei; Ko, Ying-Chin; Yen, Tzu-Chen; Chiang, Shang-Lun; Chiang, Wei-Fan; Shieh, Tien-Yu; Liao, Chun-Ta; Juang, Jyh-Lyh; Wang, Hsueh-Chun; et al. (Cancer research (Chicago, Ill.), 2014)
MicroRNAs offer tools to identify and treat invasive cancers. Using highly invasive isogenic oral squamous cell carcinoma (OSCC) cells, established using in vitro and in vivo selection protocols from poorly invasive parental cell populations, we used microarray expression analysis to identify a relative and specific decrease in miR-491-5p in invasive cells. Lower expression of miR-491-5p correlated with poor overall survival of patients with OSCCs. miR-491-5p overexpression in invasive OSCC cells suppressed their migratory behavior in vitro and lung metastatic behavior in vivo. We defined the G-protein—coupled receptor kinase-interacting protein 1 (GIT1)—as a direct target gene for miR-491-5p control. GIT1 overexpression was sufficient to rescue miR-491-5p–mediated inhibition of migration/invasion and lung metastasis. Conversely, GIT1 silencing phenocopied the ability of miR-491-5p to inhibit migration/invasion and metastasis of OSCC cells. Mechanistic investigations indicated that miR-491-5p overexpression or GIT1 attenuation reduced focal adhesions, with a concurrent decrease in steady-state levels of paxillin, phospho-paxillin, phospho-FAK, EGF/EGFR-mediated extracellular signal–regulated kinase (ERK1/2) activation, and MMP2/9 levels and activities. In clinical specimens of OSCCs, GIT1 levels were elevated relative to paired normal tissues and were correlated with lymph node metastasis, with expression levels of miR-491-5p and GIT1 correlated inversely in OSCCs, where they informed tumor grade. Together, our findings identify a functional axis for OSCC invasion that suggests miR-491-5p and GIT1 as biomarkers for prognosis in this cancer. Cancer Res; 74(3); 751–64. ©2013 AACR.